The best mistake ever! and other stories - Scarry, Richard (New York Random House, 2003)
Three stories about Lowly Worm and his friends include "The Best Mistake Ever," "A Visit to Mr. Fixit," and "Best Friends."
2
Keywords: Children's stories, American; Animals -- Fiction; Short stories